2007
DOI: 10.1080/10511482.2007.9521591
|View full text |Cite
|
Sign up to set email alerts
|

Testing a typology of family homelessness based on patterns of public shelter utilization in four U.S. jurisdictions: Implications for policy and program planning

Abstract: This study tests a typology of family homelessness based on patterns of public shelter utilization and examines whether family characteristics are associated with those patterns. The results indicate that a substantial majority of homeless families stay in public shelters for relatively brief periods, exit, and do not return. Approximately 20 percent stay for long periods. A small but noteworthy proportion cycles in and out of shelters repeatedly. In general, families with long stays are no more likely than fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
116
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 148 publications
(127 citation statements)
references
References 15 publications
6
116
2
Order By: Relevance
“…However, for adults with long-term stay patterns, other research has found little difference in outcomes between such families and their shorter staying counterparts. 46,54 This pattern is not shown here, and the differences in mortality hazard related to shelter stay patterns among families, albeit modest, are less explainable. This highlights a major limitation of this study in the unavailability of more data on personal characteristics-such as health and economic circumstances-which are likely to mitigate the associations between shelter stay patterns and mortality hazard.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…However, for adults with long-term stay patterns, other research has found little difference in outcomes between such families and their shorter staying counterparts. 46,54 This pattern is not shown here, and the differences in mortality hazard related to shelter stay patterns among families, albeit modest, are less explainable. This highlights a major limitation of this study in the unavailability of more data on personal characteristics-such as health and economic circumstances-which are likely to mitigate the associations between shelter stay patterns and mortality hazard.…”
Section: Discussioncontrasting
confidence: 52%
“…Total number of days and stays spent in DHS shelters in the 3-year period following initial shelter entry were the criteria for a cluster analysis, which was applied to data in a manner consistent with procedures previously used on DHS shelter data. 46,47 As a result, each record in this study was assigned to one of three distinct groups by virtue of shelter use patterns, with each of these groups representing different homeless trajectories. These groups included transitional users, where persons used shelter for one or two stays and for a limited number of days; long-term users, where persons used shelter for a limited number of extended stays; and episodic users, where persons tallied multiple shelter stays of relatively brief durations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies note that both the diverse characteristics of the homeless population and varying patterns of homelessness can allow for more targeted programs and policies (Sosin 2003). Other research documents the association of chronic, individual homelessness with some form of disability or other behavioral health barrier that limits successful exit from homelessness and entry into housing stability (Culhane et al 2007). Most homeless adults, however, maintain a stable exit after a short period of homelessness (Culhane et al 2007).…”
mentioning
confidence: 98%
“…Other research documents the association of chronic, individual homelessness with some form of disability or other behavioral health barrier that limits successful exit from homelessness and entry into housing stability (Culhane et al 2007). Most homeless adults, however, maintain a stable exit after a short period of homelessness (Culhane et al 2007). The literature on adult homelessness points to the limitations of stratification and individual-level explanations.…”
mentioning
confidence: 99%